Daniel and the Revelation the response of history to the voice of prophecy : a verse by verse study of these important books of the Bible - Smith, Uriah (Melbourne Vic Echo, 1902)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Daniel, Apocalyptic passages -- commentaries